Fundamentals of well-log interpretation. 1, - Serra, Oberto (Elsevier ; Elf Aquitaine, 1984)
The Acquisition of Logging Data.
Translation of: Diagraphies différées.
Keywords: Oil well logging.; elektronické knihy; electronic books